An approach for the prediction of interfacial delamination of an a-Si3N4 /Si bilayer system. (9th August 2016) - Lin, Pamela; Meng Chai, Chee; Xue, Ming; Xu, Huan; Zhou, Kun
Abstract: The prediction of interfacial delamination in multi-layered IC packaging has been a rather complex process as it is challenging to quantify the critical energies of interfacial adhesion experimentally. In this study, a combined approach based on molecular dynamics (MD) and finite element method (FEM) simulations is adopted to characterize and predict delamination in an a-Si3 N4 /Si bilayer system. The necessary material parameters that are required for the interfacial cohesive constitutive relation in FEM simulation are derived by MD simulation rather than experiment. The work of interfacial fracture obtained by the FEM simulation is about 0.11 J m −2 . To validate the presented approach, an experimental nanoindentation test is also conducted to measure the work of interfacial fracture which is obtained to be about 0.085 J m −2 . The results obtained by the MD-FEM simulations and the experiment show very good agreement. Therefore, the combined approach can also be applied to investigate other bi-materials or even multi-layered systems, thus facilitating the prediction of interfacial delamination and helping to improve the stability and reliability of the 3D multi-layered IC packaging.